PENGELOLAAN WISATA PANTAI BALONGAN DALAM UPAYA PENDISTRIBUSIAN PENDAPATAN MASYARAKAT - Muhammad Munim; Heri Kuncoro Putro; Agus Wahyu Irawan (Journal of Islamic Banking, 2023)
This research aims to determine the process and role of managing Balongan beach tourism potential towards equal distribution of community income in Balongmulyo Village, Kragan subdistrict. How is the management process carried out so that the process can achieve the targets desired by various stakeholders. The method used in this research is descriptive qualitative. The methods used in collecting data in this research were interviews, observation and documentation. The research results show that Balongan beach tourism uses a form of community-based tourism management or Community Based Tourism (CBT). This form of management prioritizes the concept of harmony between stakeholders, namely the community, government and private sector (investors). To achieve this management requires a long process, namely from the planning, implementation to maintenance stages. Then the role of managing Balongan beach tourism potential is the economic impact that is most recognized by the people of Balongmulyo, namely the equal distribution of income for the people of Balongmulyo. Because the management of Balongan beach tourism can open up employment opportunities for the people of Balongmulyo and the surrounding community by selling or as builders and increasing people's income.